EFFICACY OF THE BIOFLOC SYSTEM WITH THE ADDITION OF CHITOSAN ON TIGER PRAWN (Penaeus monodon) PRODUCTIVITY - Diana Maulianawati; Muhammad Amien; Yusriadi Pardi; Hafid Hafid; Muhammad Aditya` Rifai; Andini Aisyah Nur Raoda; Novi Luthfiyana; Syahril Syahril (SEAMEO BIOTROP, 2025)
HIGHLIGHTS- Biofloc technology with chitosan addition improved the growth performance of Penaeus monodon, increased floc volume and heterotrophic bacteria, and reduced Vibrio-like bacteria.- Biofloc technology with chitosan addition enhanced water quality and microbial community, supporting P. monodon growth.P. monodon in a biofloc system with chitosan had higher weight gain, growth rate, and survival rate. - The study provides insights for sustainable intensive shrimp farming using biofloc technology.- Findings contribute to improving productivity and maintaining environmental conditions in shrimp aquaculture. ABSTRACTPenaeus monodon farming failures are often found from Post Larva's initial distribution phase until harvest. High mortality rates of P. monodon post-larvae are often observed after stocking. A disease attack in the second month during the rearing period eventually causes failure in extensive ponds. The primary objective of this research was to investigate the impacts of adding chitosan on on the yield of P. monodon within a biofloc technology (BFT) culture system. The experiment was carried out in triplicate using three distinct treatment options. Post-larval P. monodon (PL-10) that were visually healthy and disease-free were obtained from a hatchery and then stocked at a density of 40 individuals per 100 liters. Shrimps, and fed a commercial diet four times daily for 40 days. A statistically significant difference was observed (p-value < 0.05) in weight gain (0.213-0.299 g), average daily growth (0.0054-0.0074 g/day), and specific growth rate (13.4-14.3 %/day) of shrimp were found among the treatments. The inclusion of chitosan in the biofloc system led to a prominent rise in floc volume and heterotrophic bacterial populations, while simultaneously reducing the number of Vibrio-like bacteria (VLB) colonies. No notable variations were noted in food conversion ratio (FCR), total length, survival rate, total nitrite-N, nitrate-N, and total ammonia nitrogen levels. Biofloc technology supplemented with chitosan is found to boost the growth rate of P. monodon by enhanced both water quality and the microorganisms present within it, according to the study.